The Effect of Rhodamine B on The Properties of Fluorescent Nanoparticles Derived from Geothermal Silica - Yovilianda Maulitiva Untoro; Diaz Ayu Widyasari; Edi Supriadi; Siti Nurul Aisyiyah Jenie (The Journal of Pure and Applied Chemistry Research, 2020)
Rhodamine B can be used as a fluorophore to produce a fluorescent silica nanoparticles derived from geothermal sludge. The purpose of this research is to synthesize fluorescent silica nanoparticles (FSNP) modified with rhodamine B and cetyl trimethyl ammonium bromide (CTAB) using sol-gel method. Geothermal waste was used as a precursor and added with NaOH at 900C to generate sodium silicate. Rhodamine B, as the fluorescent dye were added with concentration variations ranging from 0.156 mg/g to 10 mg/g.CTAB was used  as template and HCl 2N was applied as gelling catalyst with aging time of 18 hours. Characterization of FSNP was measured using spectrofluorometer to identify the fluorescent intensity, fourier transform infrared (FT-IR) to determine the functional group of FSNP, BraunerEmmett-Teller (BET) adsorption to calculate the specific area of the particles, X-ray diffraction (XRD) to analyze the crystallographic phases, and transmission electron microscopy (TEM) to analyze the surface morphology of the FSNP. FT-IR and fluorescent intensity results showed that FSNP with 2.5 mg/g of rhodamine B had the optimum characteristics. The FSNP was in amorphous phase with uniform pore distribution. BET analysis showed that the specific surface of the FSNP was 190.22 m2/g.